Structural and mechanistic insights into ATRX-dependent and -independent functions of the histone chaperone DAXX. Issue 1 (December 2017) - Hoelper, Dominik; Huang, Hongda; Jain, Aayushi; Patel, Dinshaw; Lewis, Peter
Abstract The ATRX–DAXX histone chaperone complex incorporates the histone variant H3.3 at heterochromatic regions in a replication-independent manner. Here, we present a high-resolution x-ray crystal structure of an interaction surface between ATRX and DAXX. We use single amino acid substitutions in DAXX that abrogate formation of the complex to explore ATRX-dependent and ATRX-independent functions of DAXX. We find that the repression of specific murine endogenous retroviruses is dependent on DAXX, but not on ATRX. In support, we reveal the existence of two biochemically distinct DAXX-containing complexes: the ATRX–DAXX complex involved in gene repression and telomere chromatin structure, and a DAXX–SETDB1–KAP1–HDAC1 complex that represses endogenous retroviruses independently of ATRX and H3.3 incorporation into chromatin. We find that histone H3.3 stabilizes DAXX protein levels and can affect DAXX-regulated gene expression without incorporation into nucleosomes. Our study demonstrates a nucleosome-independent function for the H3.3 histone variant. The ATRX-DAXX histone chaperone complex incorporates H3.3 in heterochromatin in a replication-independent manner. Here, the authors present a high-resolution x-ray crystal structure of an interaction surface between ATRX and DAXX, and characterize ATRX-dependent and-independent functions of DAXX.